Modeling stormwater management at the city district level in response to changes in land use and low impact development. (September 2017) - Kong, Fanhua; Ban, Yulong; Yin, Haiwei; James, Philip; Dronova, Iryna
Abstract: Mitigating the impact of increasing impervious surfaces on stormwater runoff by low impact development (LID) is currently being widely promoted at site and local scales. In turn, the series of distributed LID implementations may produce cumulative effects and benefit stormwater management at larger, regional scales. However, the potential of multiple LID implementations to mitigate the broad-scale impacts of urban stormwater is not yet fully understood, particularly among different design strategies to reduce directly connected impervious areas (DCIA). In this study, the hydrological responses of stormwater runoff characteristics to four different land use conversion scenarios at the city scale were explored using GIS-based Stormwater Management Model (SWMM). Model simulation results confirmed the effectiveness of LID controls; however, they also indicated that even with the most beneficial scenarios hydrological performance of developed areas was still not yet up to the pre-development level, especially where there were pronounced changes from pervious to impervious land. Highlights: Hydrological responses to changes in land use, LID controls and DCIA were captured by GIS-based SWMM at a district scale. An optimization pattern of the future urban growth is suggested by considering the LID controls and the DCIA. Addition of spatial improvement design using LIDs had a substantial positive effect on reducing stormwater flow.